Emotional Intelligence, Work Satisfaction, and Affective Commitment: An Occupational Health Study of Social Workers - Kuok, A. C. H. (Journal of Work and Organizational Psychology, 2022)
Social workers’ work engagement and burnout were tested in relation to (a) personal variable, i.e., emotional intelligence; (b) organizational variables, i.e., work satisfaction and affective commitment. Regressions revealed emotional intelligence - controlling self – negatively predicted depersonalization and reduced personal accomplishment and positively predicted three facets of work engagement. Emotional intelligence - understanding others – was a negative predictor of reduced personal accomplishment. In addition, work satisfaction negatively predicted three components of burnout and positively predicted emotional work engagement. Affective commitment was a positive predictor of three facets of work engagement and negatively predicted reduced personal accomplishment. Implications for management are discussed.

Self-Efficacy, Stress and Job Satisfaction among Pre-Service, Novice and Experienced English Teachers: A Study of their Occupational Health - Lam, Stacy; Kuok, A. C. H.; Sze, Tat Ming (Health Psychology Report, 2022)
Background This study aimed to investigate English teachers’ self-efficacy for student engagement, classroom management, instructional strategies and literacy instruction, as well as to discover teacher stress and job satisfaction can play a role in interfering their occupational health (in terms of self-efficacy). In addition, this is one of the first studies to understand the differences in self-efficacy among pre-service, novice and experienced in-service teachers in a Chinese society, where English is positioned as a foreign language. Participants and procedure 271 English teachers (90 pre-service, 181 in-service) with mean teaching experience of 5.57 months for per-service, and 98.51 months for in-service were participated in this quantitative research study, as the targets were not be able to approach randomly, the English teachers were approaching individually though referral sampling, informing that the purpose of the study and receive their consent. Results It discovered both pre-service and novice in-service teachers posses lowest self-efficacy. Moreover, teachers’ stress from classroom predicted their self-efficacy for student engagement and classroom management negatively. On the other hand, teachers’ job satisfaction predicts their self-efficacy for student engagement, instructional strategies and literacy instruction positively. Conclusions Implications (based on the findings) are discussed in order to provide insights for for schools and education departments to strengthen the teachers’ capability of teaching and their occupational health.

A positivist approach to work engagement: moderating effects of perceived organizational support - Kuok, A. C. H; Taormina, Robert J. (Dynamic Relationships Management Journal, 2022)

Elite athletes’ mental well-being and life satisfaction: a study of elite athletes’ resilience and social support from an Asian unrecognisedNational Olympic Committee - Kuok, A. C. H; K. I. Chio, David; C. H. Pun, Alan (Health Psychology Report, 2021)
Introduction This study aimed to investigate elite athletes’ mental well-being, and to ascertain whether the personal factor resilience and the social factor social support can play a role in promoting mental well-being and life satisfaction. In addition, this is one of the first studies to investigate well-being among elite athletes who are from a region belonging to an unrecognised National Olympic Committee and are not eligible to join the Olympic Games. Material and methods Eighty-four full-time elite athletes (37 males, 47 females) with mean age of 22.36 years old participated in this quantitative research study. Formal letters describing the purpose and organiser of the study were sent to the sport entities in Macao asking their permission for the researchers to contact the elite athletes to participate in this study. After gaining the permission, the elite athletes belonging to these entities were approached individually, to inform them of the purpose of the study and receive their consent. Results Regression revealed that emotional support and adaptability of resilience were strong positive predictors of mental well-being. Additionally, mental well-being was found to be a strong positive predictor of life satisfaction. The results reflected that in elite athletes possessing high adaptability and receiving more emotional support could help to maintain their mental well-being. Conclusions Implications (based on the findings) are discussed in order to provide insights for policy makers or coaches how to promote elite athletes’ mental well-being.

The Effect of Self-Efficacy and Role Understanding on Teachers’ Emotional Exhaustion and Work Engagement in Inclusive Education in Macao (SAR) - Kuok, A. C. H.; Teixeira, Vitor; Forlin, Chris; Monteiro, Elisa; Correia, Ana (International Journal of Disability, Development and Education, 2020)
This study examined responses from 508 full-time teachers working in inclusive schools in Macao (SAR). The intention was to understand the teachers’ perceptions about their roles and how they responded to inclusive practices in their school. Teachers’ perceived levels of emotional exhaustion and cognitive work engagement were assessed in relation to several professional competencies (self-efficacy with using inclusive instruction, collaborating with parents and paraprofessionals, and managing disruptive behaviours), as well as the organisational variable of role understanding. Regression analysis showed that teachers’ self-efficacy with using inclusive instruction was found to be the most powerful negative predictor of emotional exhaustion; while self-efficacy for managing disruptive behaviours was a positive predictor of teachers’ cognitive work engagement. Teachers’ level of understanding of their role and that of their schools was a negative predictor of emotional exhaustion and a positive predictor of cognitive work engagement. Moreover, it further confirmed that the concept of co-existence between work engagement and burnout can be applied to inclusive teachers. Results were interpreted in relation to management in inclusive schools in Macao and were followed by a discussion on the implications of enhancing inclusive education.

Are Work Engaged Employees Perceive Career Success? A Study of Hospitality at Macau - Kuok, A. C. H (Journal of Hospitality, 2020)
This study examined 206 casino dealers in hospitality at Macau to investigate the extent of their subjective career success and work engagement. Casino dealers were work engaged, but their subjective career success was fairly low, with significant difference between them, which indicates they have cognitive dissonance about their jobs. Several personality variables (emotional suppression and work ethic), organizational variables, i.e., organizational socialization (training, understanding, coworker support, future prospects), and distributive justice, were assessed in relation to subjective career success and work engagement. Organizational socialization, work ethic, and distributive justice were positively correlated with and predictors of subjective career success and work engagement; while emotion suppression was negatively correlated with and predictor of work engagement. This study provides evidence of extending the theories of subjective career success and work engagement in Chinese society and hospitality. Also, it identifies factors that could resolve the employees’ cognitive dissonance, and implementations for management were discussed.
Keywords: Subjective career success; emotion suppression; hospitality; human resources; socialization; work engagement

THE INTERPLAY BETWEEN A CONFUCIAN-HERITAGE CULTURE AND TEACHERS' SENTIMENTS AND ATTITUDES TOWARDS INCLUSION IN MACAU - Correia, Ana; Forlin, Chris; Teixeira, Vitor Manuel dos Santos; Kuok, A. C. H.; Monteiro, Elisa (2019)
Macau Special Administration Region (Macau SAR) is in the process of revising legislation concerning special and inclusive education. While the institutional discourse revolves around establishing inclusive education, it is unclear as to how the proposed changes will enable or depress this from occurring. This research, therefore, examined teachers’ attitudes towards inclusion as an indication of how well the new legislation may be received. Specifically, it investigated the interplay between 508 teachers working in private schools in Macau, that identified themselves as being inclusive schools, and teachers’ sentiments and attitudes towards the acceptance of inclusion and the role that Confucian values might play in shaping these attitudes. Discussion focusses on four key outcomes that need to be addressed if a significant improvement in including all children in regular schools in Macau is to be achieved. These include the need (1) to clarify the concept of inclusion at government, school, and teacher levels as it currently has ambiguous meaning; (2) to provide teachers with more opportunities to have systematic contacts with students with SEN, as this is crucial to improving their sentiments and attitudes toward people with disability; (3) to provide professional learning about inclusive education with better partnerships between teacher education institutions and schools to bridge theory and practice; and (4) to review the hidden influence of the subtle levels of time-honoured Confucian beliefs in Macau, which are not manifest nor easily detected but possibly have a deep impact on day-to-day practices.

Perceived efficacy of teachers in Macao and their alacrity to engage with inclusive education - Monteiro, Elisa; Kuok, A. C. H.; Correia, Ana; Forlin, Chris; Teixeira, Vitor (International Journal of Inclusive Education, 2019)
This paper reports findings of a mixed methods study examining private school teachers’ perceptions of efficacy in dealing with the challenges presented by inclusive education in Macao. This is highly pertinent after the Government invited consultation to propose changes to amendments of the Decree Law of 1996 concerning the education of students with Special Education Needs (SEN) which will likely see private schools being required to accept these students in the future. Within the context of teacher preparedness for inclusive education, the study found that a number of teachers felt that they were not at all prepared to teach students with SEN. Whilst some teachers suggested that they lacked skills and knowledge in teaching in inclusive classrooms, some felt overwhelmed with the challenges. The teachers proposed that they would need to know how to provide instructional adaptations and modifications to support students with SEN. Implications for continuous development of teacher training and education are discussed within the context of improving teacher efficacy and how private school teachers could better respond to the challenges of inclusive education in Macao.
Keywords: Inclusive education; Macao; teacher education; teacher efficacy

College Students’ Attitudes Toward Counseling for Mental Health Issues in Two Developing Asian Countries - Kuok, A. C. H; Rashidnia, J (Spritual Psychology and Counseling, 2019)

Placement, inclusion, law and teachers’ perceptions in Macao’s schools - Teixeira, Vitor; Correia, Ana; Monteiro, Elisa; Kuok, A. C. H.; Forlin, Chris (International Journal of Inclusive Education, 2018)
In Macao, the government has initiated a debate regarding revisions in the Decree Law in order to promote a more inclusive schooling system. In this Special Administrative Region of China, inclusive education is one of three possible types of special education that are likely be legislated in the future. The way the teachers perceive the different aspects related to inclusive education, namely the principles, concepts and law, is essential for its full implementation. The aim of this study is to understand teachers’ perceptions about the proposed amendments in the consultation document for changes in the special education regime. In particular, we focus on teachers’ acceptance of the recommended role of parents, the proposed placement models and expectations for teacher training. A mixed-methods approach with a survey of a sample of 500 teachers in private schools and interviews to a sub-sample of 20 provide the data. While agreeing in principle with the majority of the proposed changes in the Decree Law, there were several reservations made by the teachers, especially regarding the extent of parental choice, placement decisions and teacher training. Recommendations to continue the pathway for a more inclusive education system in Macao and for further research are made.
Keywords: Disability; education policy; inclusive education; special education; special education needs

The antecedents of In-service teachers’ burnout in a casino dominant economy - Kuok, A. C. H.; Lam, S. M. I (KEDI Journal of Educational Policy, 2018)

Conflict between affective versus continuance commitment among casino dealers - Kuok, A. C. H; Taormina, Robert J. (Evidence-based HRM: a Global Forum for Empirical Scholarship, 2015)
Purpose – The purpose of this paper is to empirically investigate the extent of the reported low affective commitment compared to continuance commitment of Chinese casino dealers, to discern if there is a significant difference between the two types of commitment, and to identify factors that could explain the difference between them. Design/methodology/approach – Questionnaire data were obtained from 247 Chinese casino dealers working for the three major casino groups in Macau. Correlations and regressions were used to analyze the data. Findings – Dealers’ affective commitment was significantly lower than their continuance commitment, suggesting dealers do not like their jobs but do not leave them, which indicates they have cognitive dissonance about their jobs. Organizational socialization, organizational support, and supervisor integrity were positively correlated with affective commitment; while value of money, pay satisfaction, and neuroticism, were positively correlated with continuance commitment. Organizational support was the strongest predictor of affective commitment, while the value they place on money was the strongest predictor of continuance commitment. Practical implications – Casino managers could improve dealers’ affective commitment by facilitating their organizational socialization, especially training and rewards for their work, providing greater organizational support, and fair and supportive treatment from their supervisors. Originality/value – This is the first study to provide evidence of the difference between affective and continuance commitment in Chinese society, and identifies factors that influence each type of commitment, and may help resolve the employees’ dilemma about their jobs, which is an important concern for Chinese managers.